Organic chemistry of explosives - Agrawal, J. P. (John Wiley & Son, 2007)
The book introduces the essential methods and routes used for the synthesis of organic explosives. The book consists of 4 topics. 1) the methods which can be used to introduce C-nitro, O-nitro and N-nitro functionality into organic compounds. 2) the synthesis of energetic compounds in the form of polynitropolycycloalkanes, caged and strained nitramines and N-heterocycles. 3) the sysnthesis of explosives containing functionality less widely encountered including: organic azides, peroxides diazophenols and energetic compounds derived from guanidine and its derivatives. 4) nitration with dinitrogen pentoxide and its likely significance for the future systhesis of energetic materials